Synthesis, crystal structure, theoretical calculations, and electrochemical and biological studies of polymeric (N, N, N′, N′-tetramethylethylenediamine)bis(thiocyanato-κN)copper(II), [Cu(tmeda)(NCS)2]n. (18th April 2015) - Espinosa, Arturo; Sohail, Manzar; Habib, Mehwish; Naveed, Komal; Saleem, Muhammad; Rehman, Habib-ur; Hussain, Irshad; Munawar, Aisha; Ahmad, Saeed
Graphical abstract: The crystal structure, theoretical calculations, and electrochemical and biological properties of a polymeric copper(II) complex, [Cu(tmeda)(NCS)2 ] n are presented. The polymeric structure is energetically preferred over a monomeric hydrated species, [Cu(tmeda)(NCS)2 (H2 O)]. Abstract: The title compound, [Cu(tmeda)(NCS)2 ] n (1 ) (tmeda =  N, N, N ′, N ′-tetramethylethylenediamine) was prepared by the reaction of CuCl2 ·2H2 O with potassium thiocyanate and N, N, N ′, N ′-tetramethylethylenediamine, and its structure was determined by X-ray crystallography. The crystal structure shows that the complex exists in the form of one dimensional polymer consisting of [Cu(tmeda)(NCS)2 ] units. Each Cu(II) ion is bound to two nitrogen atoms of tmeda and two nitrogen atoms and one sulfur of thiocyanate ligands adopting a distorted square pyramidal geometry. The different bonds to the metal centre are analyzed using DFT calculations that, additionally, give support to the energetically preferred polymeric structure in comparison to the monomeric or hydrated species. The electrochemical properties of the complex were studied in DMSO. Antimicrobial properties of the complex were evaluated by minimum inhibitory concentration and the results showed that the complex exhibited remarkable activities against gram-negative bacteria ( E scherichia coli, P seudomonas aeruginosa ), molds ( A spergillus niger, P enicillium citrinum ) and yeasts ( C andida albicans, S accharomyces cerevisiae ).